Interpretasi Kontekstual Abdullah Saeed: (Langkah Metodis dan Implikasi Hierarki Nilai Pada Ayat Larangan Menistakan Agama) - Anggraini, Tri Faizah (Shād : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
Saeed's efforts in offering ideas in interpretive work make a significant contribution. Basically, Saeed's thinking was inspired by Fazlur Rahman, but he provided additional inspiration in the form of a hierarchy of values ​​which is able to provide a classification of particular and universal meanings. Saeed's idea stems from his anxiety in seeing the reality of reading the text of the Koran which is carried out by sacralizing a textualist approach. This approach is considered the 'most' optimal in reading the text, thereby denying the presence of context outside the text. Due to the dominance of this textualist group, Saeed emerged to break through textual sacralization by offering a contextual approach that provides the possibility of comprehensive meaning. Based on Saeed's offer, this research also tries to apply Saaed's value hierarchy theory to the part of the verses of the Koran which discuss the prohibition of insulting religion. To explore the studies in this research, this research uses qualitative research with library research to explore the sources that are needed in the research. The primary source was obtained from Saeed's contextual interpretation book. Meanwhile, secondary sources are found in writings that have explored Saeed's thoughts and which are related to the object of research. Based on the research that has been carried out, this research found results in the form of Abdullah Saeed's thought construct which was absorbed by Fazlur Rahman's thought and the implementation of the value hierarchy in the verse prohibiting blasphemy against religion which is classified as protectional and implementational values. Keywords: Contextual, Interpretation, Abdullah Saeed.